Jawabanmu

2014-06-16T20:46:19+07:00
F(x)=px+q
f(2)=3
f(5)=4
f(17)=?

f(2)=
2p+q=3
f(5)=
5p+q=4

jadi
2p+q=3
5p+q=4
_______ -
-3p    = -1
p = -1/-3 = 1/3

umpama ambil yang f(2)
2p+q=3
2(1/3)+q=3
2/3+q=3
q=3-2/3
q=3/3-2/3
q=1/3

jadi f(17)=?
17p+q=
17(1/3)+1/3=
17/3+1/3= 18/3
18/3= 6

jadi f(17)= 6

Jawaban paling cerdas!
2014-06-16T21:01:24+07:00
Diketahui F(x) = px + q
f(2) = 3 ⇒ 2p + q = 3
f(5) = 4 ⇒ 5p + q = 4  -
                 - 3p = - 1
                     p = 1/3
2p + q = 3 ⇔ 2/3 + q = 9/3
                 ⇔ q = 9/3 - 2/3 = 7/3
f(x) = 1/3 x + 7/3
f(17) = 17/3 + 7/3 = 24/3 = 8

2 4 2